Lateral gene transfers have polished animal genomes: lessons from nematodes - Danchin, Etienne G.; Rosso, Marie-Noëlle (Frontiers in Cellular and Infection Microbiology, 2012)
It is now accepted that lateral gene transfers (LGT), have significantly contributed to the composition of bacterial genomes. The amplitude of the phenomenon is considered so high in prokaryotes that it challenges the traditional view of a binary hierarchical tree of life to correctly represent the evolutionary history of species. Given the plethora of transfers between prokaryotes, it is currently impossible to infer the last common ancestral gene set for any extant species. For this ensemble of reasons, it has been proposed that the Darwinian binary tree of life may be inappropriate to correctly reflect the actual relations between species, at least in prokaryotes. In contrast, the contribution of LGT to the composition of animal genomes is less documented. In the light of recent analyses that reported series of LGT events in nematodes, we discuss the importance of this phenomenon in the evolutionary history and in the current composition of an animal genome. Far from being neutral, it appears that besides having contributed to nematode genome contents, LGT have favored the emergence of important traits such as plant-parasitism.